Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1134/s0006297914060042
|View full text |Cite
|
Sign up to set email alerts
|

The size of the light-harvesting antenna of higher plant photosystem ii is regulated by illumination intensity through transcription of antenna protein genes

Abstract: In arabidopsis plants, with an increase in illumination intensity during growth the extent of reduction of the plastoquinone pool in the photosynthetic electron transport chain increased, whereas the effective quantum yield of photosynthesis decreased. After 5 days of growth under high illumination intensity, these parameters in high light returned to values observed in "shade-adapted" plants in low light. During the same period, the size of the antenna decreased, correlating with a decrease in the amounts of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The generation of 1 O 2 should be negligible under operation of the whole photosynthetic electron transport chain (Rutherford et al ). It can be proposed that in high light, approximately 400–700 μmol photons m −2 s −1 , when the long‐term acclimation successfully proceeds in Arabidopsis plants without resulting in a strong photoinhibition effect (Borisova‐Mubarakshina et al , our unpublished data), O 2 •− production in PSI can be prevalent over 1 O 2 production in PSII: the production of 1 O 2 is insignificant in this case. Under strong excess light conditions, more than 1000 μmol photons m −2 s −1 , a significant O 2 •− production along with significant 1 O 2 production can probably occur, triggering not only the long‐term acclimatory mechanism but also severe photooxidative stress leading to leaf bleaching, lipid peroxidation and PSII photoinhibition (Ksas et al ).…”
Section: Involvement Of the Pq Pool In The Long‐term Acclimation To Hmentioning
confidence: 90%
See 3 more Smart Citations
“…The generation of 1 O 2 should be negligible under operation of the whole photosynthetic electron transport chain (Rutherford et al ). It can be proposed that in high light, approximately 400–700 μmol photons m −2 s −1 , when the long‐term acclimation successfully proceeds in Arabidopsis plants without resulting in a strong photoinhibition effect (Borisova‐Mubarakshina et al , our unpublished data), O 2 •− production in PSI can be prevalent over 1 O 2 production in PSII: the production of 1 O 2 is insignificant in this case. Under strong excess light conditions, more than 1000 μmol photons m −2 s −1 , a significant O 2 •− production along with significant 1 O 2 production can probably occur, triggering not only the long‐term acclimatory mechanism but also severe photooxidative stress leading to leaf bleaching, lipid peroxidation and PSII photoinhibition (Ksas et al ).…”
Section: Involvement Of the Pq Pool In The Long‐term Acclimation To Hmentioning
confidence: 90%
“…The generation of 1 O 2 should be negligible under operation of the whole photosynthetic electron transport chain (Rutherford et al 2012). It can be proposed that in high light, approximately 400-700 μmol photons m −2 s −1 , when the long-term acclimation successfully proceeds in Arabidopsis plants without resulting in a strong photoinhibition effect (Borisova- Mubarakshina et al 2014, our unpublished data), O 2…”
Section: Comparing the Role Of Reaction 1 And Reaction 2 In H 2 O 2 Pmentioning
confidence: 97%
See 2 more Smart Citations
“…These data suggested that the regulation of this protein content is carried out not only at the transcriptional level, but also at the translational level. It was established that the regulation of the antenna protein synthesis can occur at both the translational level [ 40 ] and the transcriptional level [ 41 ]. The difference in the control of the content of Lhcb1 and Lhcb2 proteins included in the LHCII trimers may be of physiological significance, for example, for the adjustment of adaptive antennae rearrangements.…”
Section: Discussionmentioning
confidence: 99%